Implementation determinants of HIV Self-Testing among young sexual minority men - Juan Pablo Zapata; Andrew E. Petroll; Katherine G. Quinn; Alithia Zamantakis; Steven A. John (BMC, 2023)
Abstract Background HIV self-testing (HIVST) has shown the potential for reaching people with heightened vulnerability to HIV, including young sexual minority men (YSMM), yet implementation of HIVST among YSMM aged 17-24 is scarce as a prevention method. Moreover, despite the consistent finding that offering HIVST increases HIV testing rates, barriers remain that need to be reduced in order to maximize the potential of this biomedical technology. Such information is necessary to direct implementation efforts to increase HIVST among YSMM, including HIV counseling and linkage to care. The current study was therefore intended to investigate perspectives for HIVST among YSMM and how HIVST can be marketed to increase implementation. Methods Between March and September 2020, we enrolled 41 YSMM to participate in one of nine online synchronous focus group discussions about their general experience with HIV preventive services. Guided by the Consolidated Framework (CFIR) for Implementation Research, we explored YSMM perspectives on facilitators and barriers to HIVST implementation. Data were analyzed using a deductive thematic content analysis approach. Results Many participants had never used HIVST before their participation in this study (n = 30; 73.2%). Qualitative results exhibited a variety of implementation determinants across the five CFIR 2.0 domains. Barriers included concerns about the format in which the testing materials would be provided (i.e., nature of packaging) and about the method in which the sample would need to be collected, particularly for those who had the testing kit mailed to their home address. These reservations were nested in the fear of unwanted disclosure of their sexual behavior, namely among the respondents who had to cohabitate with family due to the COVID-19 pandemic. Participants also discussed the limited local resources for HIVST. Many participants suggested programs that could be implemented to support HIVST, such as collaborations with trusted community agencies. Conclusions Understanding YSMM' perspectives of HIVST may help identify implementation deficiencies within the delivery system and aid the development of implementation strategies to promote reach of HIVST.